Whole-body cryotherapy multi exposures speed up performance supercompensation during the taper in functionally overreached endurance athletes - Le Meur, Y.; Louis, J.; Schaal, K.; Bieuzen, F.; Filliard, J.-R.; Brisswalter, J.; Hausswirth, C. (Sport Performance & Science Reports, 2017)
In many endurance sports, the competitive season involves a series of events that can stretch over several weeks or months (e.g. cycling, triathlon, biathlon). The resulting combination of frequent competitions with short tapers largely increases the risk of functional overreaching (F-OR) resulting in a decline in performance. Even though the F-OR state is generally reversed when an appropriate period of recovery is provided (1-2 weeks), it can compromise the competition outcome in the short term. A recent study suggested that daily whole-body cryotherapy (WBC) exposures may mitigate the signs of F-OR during intensified training blocks (i.e. reduced sleep quantity, increased fatigue, and impaired exercise capacity) (1) but more research remains required to confirm this finding. Aim. This aim of the present study was to investigate whether multiple WBC exposures would represent a convenient tool for recovering from F-OR by speeding up the performance supercompensation during a 1-week taper programmed after a heavy load training period in well-trained endurance athletes.